Development of a software kit and real-time monitoring system for open WRT-based mobile robots - Camongol, Khristian Rey M.
More innovative ways of controlling mobile robots are being seen nowadays. Common embedded devices are being hacked and tapped for other uses by altering some of their hardware and/or modifying their firmware. Of particular importance are wireless routers which are embedded devices which are primarily meant for communication. With a little tweaking, they could do other productive tasks. Since they possess both enough processing power and seamless wireless communications capabilities, they are now being tapped in many hobby projects nowadays. Programming them, however, takes considerable time as there is no one-click solution as of now. Monitoring such robots is another issue. Given their built-in communication capabilities, a readily-available interface can be built upon them to check their status easily. The long process of programming an Open WRT custom firmware wireless router will be automated, while a web interface will be put inside the router, to provide real-time sensor update. Those two tools make up this Software Kit. The SK will help the future users of wireless router to easily program and monitor them, a crucial thing in applications like localization and mapping.